THE RESPONSE TO PREOPERATIVE (NEOADJUVANT) CHEMOTHERAPY AND RADIOTHERAPY IN LOCALLY ADVANCED RECTAL CANCER (Journal of Pharmaceutical Negative Results, 2022)
To find out how well pre-operative (neo-adjuvant) chemoradiotherapy works for patients with locally advanced rectal cancer by looking at how often the cancer comes back after surgery in the same area. Follow-up continues until November 2019. The research required appropriate biochemistry, pathology, radiography, and medical/surgical management. Since June 2019, outpatients are assessed. Rectal cancer research studied age, sex, diagnosis delay, mortality, treatment options, death causes, surgical complications, and hospital stay. Typical, pre-validated, semi-structured case record proformas recorded the data. CBC, biochemical profile, serological sample, upright abdominal X-ray, CT scan, transrectal, pelvic, or abdominal ultrasound. After staging, patients received chemotherapy (625 mg/m2 capecitabine orally in 4 doses) and radiation (50.4 Gy in 28 parts) and were reevaluated for surgery after 4 weeks. Post-neoadjuvant therapy, 52.5% of patients underwent anterior resection, 37.5% underwent LAR, and 10% underwent APR. To make neoadjuvant treatment standard, more experience, competence, and patients are needed.